Implementation of the PIMCA model to learning convex mirror - Reskin, S; Silangen, P M; Tumangkeng, J V; Poluakan, C; Londa, T K; Mondolang, A H (Journal of physics. Conference series, 2021)
Learning in the 4.0 era requires various learning models, one of which is the MR-SR based PIMCA learning model (Presentation, Idea Mapping, Conceptualization, Assessment Formative) which presents the same concept in several formats. This study aims to determine the increase in student learning outcomes before and after implementing the MR-SR based PIMCA learning model introduced and developed by Cosmas Poluakan. The research method used of One group pre-test post-test design. This research of conducted in the Department of Physics, State University of Manado, with 29 student respondents. The research process begins with problem formulation, management, analysis of data, and conclusion. The results of the data analysis showed that the average score before the test of 20,69 and the average score after the test is 72,41. With a maximum value of 75, a gain of 0.9 is obtained. This means that there is an increase in learning outcomes in the high category because g > 0,7. The results of this study indicate that the MR-SR based PIMCA learning model can improve student learning outcomes in mastery of physics concepts.